(untitled) (NAU Journal of Technology and Vocational Education, 2024)
In the recent times, implementation of office technology and management (OTM) curriculum largely depends on ICTs instructional competencies. Therefore, this study determined the level of ICT instructional competencies possessed by lecturers for implementing OTM curriculum in public tertiary institutions in Rivers State. One research question guided the study and three null hypotheses were tested. Descriptive survey research design was adopted. From a population of 69 OTM lecturers, the census survey sampling was employed. A five-point response options questionnaire was used for data collection, and it was validated by expert. The reliability of the instrument was established using Cronbach’s alpha which yielded a alpha coefficient of 0.93. Mean was used to answer the research question, while one-way analysis of variance (ANOVA) and t-test were used to test the null hypotheses at 0.05 level of significance. Findings revealed that the lecturers possessed ICTs instructional competencies at a high level for the implementing OTM curriculum. The lectures do not differ significantly in the level they possessed ICTs competencies for OTM curriculum implementation based on their level of education, teaching experience and institution ownership. Therefore, it was recommended that OTM lecturers should conciously engage in further ICTs trainings to sustain and improve their ICTs instructional competencies for effective curriculum implementation in their areas of operations.